Development of a Cloud-Based Religious School Management Information System to Facilitate School Data Management at SD Muhammadiyah Kadisoka - -, Helga Parama Zhafran; Hidayat, Syarif (AUTOMATA, 2026)
Digital transformation in education continues to expand, yet many schools in Indonesia still lack the infrastructure, financial capacity, and technical expertise needed to operate conventional information systems. These limitations often leave institutions dependent on fragmented paper records, offline spreadsheets, or government reporting tools such as Dapodik, which do not support daily operations or provide access for teachers, students, and parents. Motivated by these constraints, this study applies a case-based engineering approach to design and validate a cloud-based School Information Management System for a resource-limited religious school. Google Apps Script, Google Sheets, and Google Drive were selected over server-based alternatives due to their zero-cost serverless execution, native integration, minimal maintenance requirements, and usability for non-technical staff. WhatsApp automation was implemented through the Wablas API to leverage the platform’s dominant role in school–parent communication. The resulting system provides modules for student and teacher data management, class scheduling, document submission, academic grading, dashboards, and automated notifications. Development followed the Waterfall model, while validation included black-box testing of functional requirements and a System Usability Scale (SUS) assessment involving administrators, teachers, and student guardians. All functional tests passed, and the SUS evaluation indicated acceptable usability. The findings demonstrate that a serverless, Google-ecosystem stack can deliver a reliable, scalable, and affordable management system for schools that cannot operate local servers and require a lightweight digital solution to replace manual workflows.